Single-cell RNA sequencing unraveled immune-related expression heterogeneity and lymphoid cell development dysregulation in childhood asthma - Zhu, Danying; Li, Guang; Yuan, Lang; Zeng, Zeyu; Dong, Na; Wang, Chao; Chen, Ming; Xie, Lijian; Ding, Guohui; Shen, Libing; Dong, Xiaoyan (Frontiers in Immunology, 2026)
BackgroundsAsthma is a chronic inflammatory disease affecting airways, usually starting in childhood. Its cause remains unclear.ObjectiveWe aim to elucidate the role of immune dysregulation in the pathogenesis of pediatric asthma.MethodsIn this study, we used single-cell RNA sequencing to analyze peripheral blood mononuclear cells (PBMCs) from three pediatric asthma patients and four age-matched healthy controls to investigate the cellular etiology of childhood asthma.ResultsThe overall expression patterns of PBMCs from the three asthma patients indicate that both innate and adaptive immunity are imbalanced and abnormally activated in childhood asthma. Analysis of hematopoietic stem and progenitor cells (HSPCs) expression profiles further reveals that HSPCs from asthma patients tend to express immunity-related genes earlier. The cell developmental trajectories observed in asthma patients show an abnormal immune cell development pattern. Dysregulated lymphoid lineage development is observed in all three patients but there is no identical abnormal pattern for each patient. Pseudo-time analysis of gene expression demonstrates that JUN, a gene controlling cell cycle progression, is repressed in asthma patients while SPI1, an essential gene for lymphoid lineage development along with six inflammatory response related genes (S100A8, S100A9, S100A12, IL7R, IL32, and CCL5), exhibit various aberrant expression trajectories in asthmatic individuals. S100A8, S100A9, S100A12, and RETN are universally upregulated in various cell types of asthma patients. The analyses of cell-cell communication further elucidate the contributory roles of dendritic cells and CD14+ monocytes in the development and heterogeneity of asthma, as they exhibit increased reception and transmission of annexin and resistin signals in the asthma group. The resistin protein-protein interaction network analysis further suggests that SQSTM1, HSPA5 and A2M might serve as the potential therapeutic targets in childhood asthma.ConclusionsOur scRNA-Seq analyses unveil childhood asthma as a complex disease with immune-related heterogenicities, characterized by dysregulated lymphoid cell development, a common feature that may offer a novel research direction for comprehensively understanding the key molecular mechanisms underlying childhood asthma.